Gene Gun-Mediated DNA Immunization Primes Development of Mucosal Immunity against Bovine Herpesvirus 1 in Cattle - Loehr, B. I. (American Society for Microbiology, 2000)
Vaccination by a mucosal route is an excellent approach to the control of mucosally acquired infections. Several reports on rodents suggest that DNA vaccines can be used to achieve mucosal immunity when applied to mucosal tissues. However, with the exception of one study with pigs and another with horses, there is no information on mucosal DNA immunization of the natural host. In this study, the potential of inducing mucosal immunity in cattle by immunization with a DNA vaccine was demonstrated. Cattle were immunized with a plasmid encoding bovine herpesvirus 1 (BHV-1) glycoprotein B, which was delivered with a gene gun either intradermally or intravulvomucosally. Intravulvomucosal DNA immunization induced strong cellular immune responses and primed humoral immune responses. This was evident after BHV-1 challenge when high levels of both immunoglobulin G (IgG) and IgA were detected. Intradermal delivery resulted in lower levels of immunity than mucosal immunization. To determine whether the differences between the immune responses induced by intravulvomucosal and intradermal immunizations might be due to the efficacy of antigen presentation, the distributions of antigen and Langerhans cells in the skin and mucosa were compared. After intravulvomucosal delivery, antigen was expressed early and throughout the mucosa, but after intradermal administration, antigen expression occurred later and superficially in the skin. Furthermore, Langerhans cells were widely distributed in the mucosal epithelium but found primarily in the basal layers of the epidermis of the skin. Collectively, these observations may account for the stronger immune response induced by mucosal administration.